ASSOCIATION OF LIPOPROTEIN-Î± WITH OBESITY IN CHILDREN AND ADOLESCENTS IN DISTRICT SWAT - Shah, Syed Motahir Ali; Ihsanullah, Mian; Rasheed, Abdur (Journal of Ayub Medical College Abbottabad, 2009)
Background: Studies have demonstrated that atherosclerosis has its silent beginning during childhood. Coronary artery disease, particularly when it presents early in adult life has been observed to have a familial tendency. Lipoprotein-Î± [Lp-Î±], has a strong genetic association and raised levels when combined with obesity increase the risk of premature coronary heart disease. Thus in adults, has emerged the possibility of preventing or delaying the coronary artery disease when appropriate measures are applied early in life. In our study, we assessed the prevalence of overweight and obesity and its association with Lp-Î± in the child population of district Swat. Methods: The study was carried out in Saidu Teaching Hospital and Biochemistry Department, Saidu Medical College, Swat, from May to July 2007. Both boys and girls between 10-20 years of age were included. The prevalence of obesity was detected in 200 subjects by using body mass index. One hundred subjects were selected to compare the anthropometric and cardiovascular parameters of obese subjects with control group. Lp-Î± was measured in children of both the groups. Results: The prevalence of obesity in adolescent boys was 6.7% and that in adolescent girls was 10%. The prevalence was higher in female subjects, compared to male subjects. Obese subjects had significantly higher weight, body mass index, blood pressure values and Lp-Î± levels as compared to control group. Conclusion: Lipoprotein-Î± level is higher in obese children and adolescents than in non-obese. Keywords: Lipoprotein-Î±, Lp-Î±, Body mass index (BMI), Blood pressure (BP), Obesity